Rising Food Prices in East Asia : Challenges and Policy Options - Brahmbhatt, Milan; Christiaensen, Luc (World Bank, Washington, DC, 2014)
Large increases in international food prices in 2007 and early 2008 have become a key concern for policy makers in East Asia. The increases are likely to have a significant impact on the living standards of many, particularly the poor. By March 2008, dollar nominated world food prices were more than two and a half times higher than in early 2002. Almost three quarters of this increase occurred since the start of 2007, and about half since the beginning of 2008. Recent sharp increases in international rice prices are of particular concern in East Asia. Food comprises 30 to 50 percent of the consumption basket of the average household in East Asia (compared to 15 percent in the United States). Within that, rice accounts for one third of the daily caloric intake, followed by wheat (12.4 percent), pork (8.8 percent), corn (4.4 percent), soybean and palm oil (3.4 percent and 1.8 percent respectively). This note examines the reasons for the surge in world food prices, in particular of rice in section two. It reviews the economic and poverty impacts of rising food prices in East Asian countries in section three. Finally, it concludes by assessing policy responses undertaken by East Asian economies so far, and discusses policy options going forward, including the importance of regional and international cooperation in addressing high food prices in section four.